The Effects of Buddhist Meditation Therapy Program on Life Happiness of the Elderly with Hypertension at a Community in Phetchaburi Province - ฤาเดช, รพีพร; นิมิตรอานันท์, นงพิมล; รุจนเวช, ศศิธร (Journal of The Royal Thai Army Nurses, 2018)
This research was a quasi-experimental study two group pretest-posttest design. The purpose was to examine the effects of Buddhist meditation therapy program on life happiness of the elderly with hypertension.The subjects were 52 older persons with hypertension. They had been sampling by multi – stage, random sampling technique and divided into an experimented and a comparison group on 26 cases each. The experimental group received the 8-week Buddhist meditation therapy program which applied Watson’s Caring Theory and chronic care model with Buddhist integration. This program consisted of 1) trust establishment 2) interpersonal relationship promotion 3) home-based environment support and 4) knowledge sharing. Data collection used demographic data, self-care behavior, and life happiness scores. The reliability was at 0.75 and 0.84 respectively. Data were analyzed using descriptive statistics and t - test. The results revealed that after the intervention, the experimental group had significantly higher mean scores of self-care behavior and life happiness than before the intervention, and than those in the comparison group, while the experimental group had significantly lower mean scores of blood pressure than before the intervention and than the comparison group. The researcher recomment that the Buddhist meditation therapy program is effectively enhance happiness for the elderly with hypertension. Therefore, nurse practitioners and healthcare providers should contribute this program in primary care service for caring the elderly with hypertension to promote life happiness and well-being.